2020
DOI: 10.1089/thy.2019.0269
|View full text |Cite
|
Sign up to set email alerts
|

An International Phase 2 Study of Pazopanib in Progressive and Metastatic Thyroglobulin Antibody Negative Radioactive Iodine Refractory Differentiated Thyroid Cancer

Abstract: ; the Mayo Phase 2 Consortium Introduction: Multikinase inhibitors have clinical activity in radioactive iodine refractory (RAIR) differentiated thyroid cancers (DTCs) but are not curative; optimal management and salvage therapies remain unclear. This study assessed clinical effects of pazopanib therapy in RAIR-DTC patients with progressive disease, examining in parallel biomarker that might forecast/precede therapeutic response. Methods: Assessment of responses and toxicities and of any association between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…However, the dose of L-T4 could be reduced to 62.5 μg/d since C28, indicating the distribution or utilization of L-T4 might be influenced by anlotinib, it also reminds clinicians to be aware of this problem and implement measures to minimize the occurrence of overdosing and the potential for long-term complications. Interestingly, Bible et al ( 5 ) observed TSH levels increased by >15% between baseline and cycle one/4 weeks reassessment in 64.6% of RAIR-DTC patients treated with pazopanib, indicating that early TSH increment is frequent in response to pazopanib therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the dose of L-T4 could be reduced to 62.5 μg/d since C28, indicating the distribution or utilization of L-T4 might be influenced by anlotinib, it also reminds clinicians to be aware of this problem and implement measures to minimize the occurrence of overdosing and the potential for long-term complications. Interestingly, Bible et al ( 5 ) observed TSH levels increased by >15% between baseline and cycle one/4 weeks reassessment in 64.6% of RAIR-DTC patients treated with pazopanib, indicating that early TSH increment is frequent in response to pazopanib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…RAIR-DTC is insensitive to conventional chemotherapy. Many targeted drugs [including donafenib ( 4 ), pazopanib ( 5 , 6 ), cabozantinib ( 7 ), vandetanib ( 8 ), axitinib ( 9 ), sunitinib ( 10 ), motesanib ( 11 )] are increasingly being used to treat RAIR-DTC due to many signaling pathways and gene mutations that driving thyroid tumorigenesis have been identified. Although sorafenib and lenvatinib have been approved by the U.S. Food and Drug Administration to be used in RAIR-DTC, not all patients have access to or are able to afford those drugs ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…В то же время вероятность ответа на лечение данным препаратом на основании оценки исследуемых биомаркеров, предшествующей терапии или мутационного статуса опухоли спрогнозировать не удалось. Исследователи подчеркнули, что результаты являются обнадеживающими, однако достоверных доказательств его эквивалентной, превосходящей или недостаточной эффективности по сравнению с другими ТКИ при рефрактерном к РЙТ дифференцированном РЩЖ по-прежнему отсутствуют [38].…”
Section: таргетные препаратыunclassified
“… 96 Other agents under investigation include axitinib, pazopanib, and sunitinib. 97 , 98 Kinase inhibitor therapy is often limited by its side-effect profile, which includes nausea, diarrhea, fatigue, weight loss, hand-foot syndrome, hypertension, and QTc prolongation, so medical comorbidities should be assessed prior to therapy. 12 , 18 , 43 , 99 , 100 Although significant, treatment-emergent hypertension in lenvatinib therapy has been correlated with improved outcomes.…”
Section: Systemic Therapymentioning
confidence: 99%